2019
DOI: 10.5194/acp-19-7319-2019
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric evolution of molecular-weight-separated brown carbon from biomass burning

Abstract: Abstract. Biomass burning is a major source of atmospheric brown carbon (BrC), and through its absorption of UV/VIS radiation, it can play an important role in the planetary radiative balance and atmospheric photochemistry. The considerable uncertainty of BrC impacts is associated with its poorly constrained sources, transformations, and atmospheric lifetime. Here we report laboratory experiments that examined changes in the optical properties of the water-soluble (WS) BrC fraction of laboratory-generated biom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
168
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(212 citation statements)
references
References 76 publications
18
168
3
Order By: Relevance
“…Moreover, Saturno et al (2018b) have shown that the brown carbon (BrC) contribution to total absorption becomes increasingly important towards the end of the dry season. This is a further indication of the predominance of regional fires towards the later BB season, given that BrC is quickly photodegraded in the atmosphere after emission, with a typical lifetime of few days to weeks (Fleming et al, 2019;Wong et al, 2019), comparable to the transport times of African BB emissions 680 across the Atlantic.…”
Section: Estimated Relevance Of Pollution Layer For Central Amazonianmentioning
confidence: 92%
“…Moreover, Saturno et al (2018b) have shown that the brown carbon (BrC) contribution to total absorption becomes increasingly important towards the end of the dry season. This is a further indication of the predominance of regional fires towards the later BB season, given that BrC is quickly photodegraded in the atmosphere after emission, with a typical lifetime of few days to weeks (Fleming et al, 2019;Wong et al, 2019), comparable to the transport times of African BB emissions 680 across the Atlantic.…”
Section: Estimated Relevance Of Pollution Layer For Central Amazonianmentioning
confidence: 92%
“…S7). Recent aircraft measurements of African BB pollution over Ascension Island have found similar EnR BC,M = 11-17 ng m −3 ppb −1 in the free troposphere (Wu et al, 2020). The ozone as a secondary pollutant also presents a maximum within the UPL (c O 3 = 56±9 ppb) and appears to be anti-correlated with NO (c NO = 0.10±0.02 ppb).…”
Section: Offshore Aerosol Particle and Trace Gas Profilesmentioning
confidence: 85%
“…OC, EC and σ abs data used in this study are available from the corresponding authors upon request. Data analysis and visualization toolkits (Histbox, MRS and Scatter Plot) used in this study are available at https://doi.org/10.5281/zenodo.832405 (Wu, 2020a), https://doi.org/10.5281/zenodo.832395 (Wu, 2020b) and https://doi.org/10.5281/zenodo.832416 (Wu, 2020c), respectively.…”
Section: Discussionmentioning
confidence: 99%